Introduction to cosmology - Ross, Matts (Chichester, John Wiley & Sons Ltd., 2003)
The Third Edition of the hugely successful Introduction to Cosmology provides a concise, authoritative study of cosmology at an introductory level. Starting from elementary principles and the history of cosmology, the text carefully guides the student on to curved spacetimes, general relativity, black holes, cosmological models, particles and symmetries, and phase transitions. Extensively revised, this latest edition includes broader and updated coverage of distance measures, gravitational lensing and waves, dark energy and quintessence, the thermal history of the Universe, inflation, large scale structure formation, and the 'cosmological coincidence'problem.* Illustrated throughout and comprehensively referenced with problems at the end of each chapter.* Includes more material on observational astrophysics and expanded sections on astrophysical phenomena.* Latest observational results from the WMAP satellite and the 2 degree Field Galaxy Redshift Survey.
Includes bibliographical references; Index 271-279p.